2007
DOI: 10.1093/jxb/erl263
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of MADS box genes involved in the determination of oil palm flower structure

Abstract: In order to study the molecular regulation of flower development in the monoecious species oil palm (Elaeis guineensis), cDNAs of 12 MADS box genes from this plant belonging to seven distinct subfamilies were previously isolated and characterized. Here studies carried out on five of these genes, each likely to be involved in floral morphogenesis: EgSQUA1 (SQUAMOSA subfamily); EgAGL2-1 (AGL2 subfamily); EgGLO2 (GLOBOSA subfamily); EgDEF1 (DEFICIENS subfamily); and EgAG2 (AGAMOUS subfamily), are described. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 62 publications
5
46
1
2
Order By: Relevance
“…3). The expression in organs other than flowers has also been reported in some B class genes such as GDEF1 (G. hybrida), TGGLO (T. gesneriana), ZMM16 (Z. mays), and EgGLO2 (Elaeis guineensis) that showed a similar expression pattern to OMADS8/3 by expressing in both flower organs and leaves (Yu et al, 1999;Mü nster et al, 2001;Kanno et al, 2003;Adam et al, 2007). This revealed that in addition to regulating flower organ formation, B class genes such as OMADS3/8, GDEF1, TGGLO, ZMM16, and EgGLO2 are also possibly involved in the regulation of leaf development.…”
Section: Discussionmentioning
confidence: 75%
“…3). The expression in organs other than flowers has also been reported in some B class genes such as GDEF1 (G. hybrida), TGGLO (T. gesneriana), ZMM16 (Z. mays), and EgGLO2 (Elaeis guineensis) that showed a similar expression pattern to OMADS8/3 by expressing in both flower organs and leaves (Yu et al, 1999;Mü nster et al, 2001;Kanno et al, 2003;Adam et al, 2007). This revealed that in addition to regulating flower organ formation, B class genes such as OMADS3/8, GDEF1, TGGLO, ZMM16, and EgGLO2 are also possibly involved in the regulation of leaf development.…”
Section: Discussionmentioning
confidence: 75%
“…There appears to have been a substantial amount of functional diversification in the SEP-like and AG-like subfamilies, given the number of new transcripts found compared with those observed previously in studies of the oil palm flower structure (Adam et al, , 2007a(Adam et al, , 2007b. This diversification appears to have arisen through the expansion of the expression of genes that either have retained a function in the flower or have specialized functions within the fruit.…”
Section: Profiles Of Tfs and Transcription Regulators In The Mesocarpmentioning
confidence: 81%
“…Where they used Spidey algorithm to predict the gene position with mRNA sequenced, using mRNA data with accession number AF411848.1 from the study by Adam et al (2007), and whole DNA sequence, using a genome region data with accession number NW_011550962.1 from the study of Singh et al (2013). According to PerlPrimer (application for designs primers, ORF and CpG island detection algorithms) analysis of globosa gene were separated into seven exons, between each exon are introns (Figure 2.).…”
Section: Resultsmentioning
confidence: 99%
“…The study about genes taking part in controlling and developing flowering organ had been conducted by Adam et al (2007), which showed that the flowering process was controlled by MADS-box gene. In their study, Adam et al used cDNA samples to characterize MADS-box gene of palm oil.…”
Section: Introductionmentioning
confidence: 99%